علامہ محمد اقبال اور سر سیداحمد خان کے مابعد الطبیعیاتی تصورات کا تقابلی مطالعہ: Concepts of Metaphysics by Allama Muhammad Iqbal and Sir Sayyid Ahmad Khan: Comparative Study - Muhammad Mazhar Saeed,; Dr. Shahid Iqbal Kamran, (MEI, 2023)
Allama Muhammad Iqbal and Sir Syed Ahmad Khan were the prominent personalities of their eras. Both have worked on the concept of metaphysics and had given a new approach of metaphysics to the Muslim Society. The ideas of both the sages were clear, comprehensive and detailed and based Quran as primary source of knowledge. In this regard Sir Syed Ahmad Khan wrote his famous Tafseer-ul-Quran. Allama Iqbal gave a special place to the traditions of Prophet (PBUH) regarding metaphysics but Sir Syed Ahmad Khan abstained from referring the same. A detailed analysis of ideas of metaphysics of both the personalities is given in detail